Implementasi Pembelajaran Blended Learning Berbasis Media Google Classrom Terhadap Hasil Belajar Mahasiswa Pendidikan Fisika - Setyoko Setyoko; indriaty indriaty (Jurnal Pendidikan Fisika dan Sains, 2018)
Abstract Merging between conventional learning through face-to-face and online media is very possible to produce effective and meaningful learning for students. The purpose of this study was to determine the effect of the implementation of Blended Learning on improving the learning outcomes of physics education students. This study used a quasi-experimental method with a non-equivalent research design pretest-posttest control group design. The sample of this study was the second semester students of the Samudra University Physics Education who attended the Educational Philosophy course. The sample consisted of 1 class unit and 25 people. The research instruments included the pretest and posttest tests. The results obtained by the value of t count of 8.14 or with Sig (2 -tailed) (0.00) ≥ α (0.05) thus accept Ha and reject H0. This shows that there is the influence of the use of the Google Classroom-based Blended Learning learning model for improving the learning outcomes of physics education students Keywords: Blended Learning, Google classroom, Learning outcomes